2013
DOI: 10.5539/ies.v6n11p58
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Instructional Strategies of Elementary School Teachers When Developing Technological, Pedagogical, and Content Knowledge via a Collaborative Professional Development Program

Abstract: The technological, pedagogical, and content knowledge (TPACK) framework has been regarded as potentially effective in helping teachers integrate technology into the classroom. This study explores the instructional strategies of teachers when developing TPACK. A teacher professional development (TPD) program, in which teaching activities and deep discussions were key processes, was conducted. Instructional observations and focus-group interviews were the primary evaluation methods. Six elementary school teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 34 publications
2
14
0
5
Order By: Relevance
“…Unlike young teachers who may have abundant technology skills, the senior teacher developed a TPACK framework on the foundation of her current PCK, as evidenced by previous studies (Graham et al, 2012;Koh & Divaharan, 2011;Liu, 2013), indicating that experienced teachers typically focus on subject content and instructional strategies when integrating technology.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Unlike young teachers who may have abundant technology skills, the senior teacher developed a TPACK framework on the foundation of her current PCK, as evidenced by previous studies (Graham et al, 2012;Koh & Divaharan, 2011;Liu, 2013), indicating that experienced teachers typically focus on subject content and instructional strategies when integrating technology.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Regarding senior teachers, studies have demonstrated that the pedagogical knowledge of in-service teachers encourages their integration of ICT (Harris, Grandgenett, & Hofer, 2010;Liu, 2013). Moreover, other studies have proposed that in-service teachers were mainly concerned with subject content when they integrated technology into their instruction (Graham, Borup, & Smith, 2012;Koh & Divaharan, 2011;.…”
Section: Ability Of Senior Teachers To Integrate Technology Into Instmentioning
confidence: 99%
“…Studies of teachers' TPACK that focused on technology integration broadly across subject areas underscored that teachers generally needed to develop Technological Pedagogical Knowledge or Technological Content Knowledge (Boschman et al, 2015;Finger & Finger, 2013;Graham et al, 2012;Hofer & Grandgenett, 2012;Liu, 2013). However, studies of teachers TPACK in a particular content area underscored the need for teachers to specifically develop Technological Content Knowledge (Hughes & Scharber, 2008;Maeng et al, 2013;Ozgun-Koca et al, 2011).…”
Section: Teachers' Demonstrations Of Tpackmentioning
confidence: 99%
“…Por último, se demuestra la importancia del marco TPACK a partir de la valoración de las acciones formativas emprendidas para la instrucción del docente en TIC, que hacen algunos autores (Marks, 1990;Hu, Walker y Hsiao, 2013;Liu, 2013 Hu, 2014). Como ejemplo de estas valoraciones pueden citarse las palabras de Marks (1990), quien señala que:…”
Section: Conocimiento Tecnológico Pedagógico Del Contenido (Tpack)unclassified